A new species of Myiopharus Brauer and Bergenstamm (Diptera: Tachinidae) parasitic on adults of the sunflower beetle, Zygogramma exclamationis (Fabricius) - O’hara, James E. (Zootaxa, 2007)
A new species of the New World genus Myiopharus Brauer and Bergenstamm, Myiopharus neilli sp. nov., is described from the Great Plains, bringing the number of species of this genus known from America north of Mexico to 15. Myiopharus neilli is a parasitoid of adults of the sunflower beetle, Zygogramma exclamationis. It belongs to the M. dorsalis (Coquillett) species group, the females of which possess a strongly sclerotized and laterally flattened ovipositor and a dense tuft of blunt setae medially on the katepisternum. Both sexes of M. neilli are described and illustrated, the life history of the species is reviewed, and the M. dorsalis group is characterized.